1980
DOI: 10.1111/j.1744-7348.1980.tb03964.x
|View full text |Cite
|
Sign up to set email alerts
|

Cabbage stem weevil (Ceutorhynchus quadridens) on spring oilseed rape in Southern England and its control

Abstract: S U M M A R YSurveys in 1974-75 in which 20 plants were examined in each of 105 fields showed that cabbage stem weevil was widespread on spring oilseed rape in the south of England, the larvae sometimes infesting a large percentage of plants and reducing vigour and yield. In replicated field trials during 1974-77, infestations were reduced by seed treatments of gamma-HCH or sprays of gamma-HCH, azinphos-methyl, azinphos-methyl + demeton-S-methyl sulphone, chlorpyrifos or triazophos. In some experiments treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…Adult C. pallidactylus were abundant in early April, thereafter declining throughout May and June (Figure 1a). This timing concurs with the few other studies on this pest in the UK, e.g., on winter oilseed rape , on seedlings of Trowse mustard (Brassica juncea) (Winfield, 1961) and on spring oilseed rape (Graham and Gould, 1980). Graham and Gould (1980) suggested that winter oilseed rape was not damaged by C. pallidactylus but since then, Ferguson et al (2003) have reported stem injury to winter rape by this pest.…”
Section: Phenology Of Stem-mining Pests Of Oilseed Rape and Their Parsupporting
confidence: 78%
See 2 more Smart Citations
“…Adult C. pallidactylus were abundant in early April, thereafter declining throughout May and June (Figure 1a). This timing concurs with the few other studies on this pest in the UK, e.g., on winter oilseed rape , on seedlings of Trowse mustard (Brassica juncea) (Winfield, 1961) and on spring oilseed rape (Graham and Gould, 1980). Graham and Gould (1980) suggested that winter oilseed rape was not damaged by C. pallidactylus but since then, Ferguson et al (2003) have reported stem injury to winter rape by this pest.…”
Section: Phenology Of Stem-mining Pests Of Oilseed Rape and Their Parsupporting
confidence: 78%
“…The pest status and phenology of C. pallidactylus has been less studied in the UK than in continental Europe, although there are some observations of its incidence on both winter and spring (Winfield, 1961;Graham and Gould, 1980) oilseed rape. Adults migrate to winter oilseed rape in early spring (Bonnemaison, 1965;Walczak et al, 1998;Ferguson et al, 2003); in the UK, Ferguson et al (2003) caught them in flight traps from 20 April until 20 June.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The economic threshold for the two weevil species varies among different regions and is based on their abundance and damage capabilities. For the cabbage stem weevil a threshold of 10–20 specimens per yellow water trap within three consecutive days is usually acceptable for Central Europe, while for the rape stem weevil a threshold of ten specimens per yellow water trap within three consecutive days is used . Other authors mention different thresholds of 4–6 rape stem weevil specimens and 12 cabbage stem weevil specimens for the same monitoring conditions .…”
Section: Methodsmentioning
confidence: 99%
“…Stem weevils can cause significant yield losses, and some authors indicate that they can vary from 5% 9 to 32% or more, accounting for a loss of up to 800 kg ha −1 . Even cases with larval presence on 100% of plants are recorded …”
Section: Introductionmentioning
confidence: 99%